Multilingualism In The Linguistic Landscape Of Coffee Shops In Surakarta - Ricardo, Pradana; Larasanti , Fadhilah; Yustanto, Henry (Journal of Language and Applied Linguistics, 2026)
This study aims to describe the use of multiple languages in the linguistic landscape of coffee shops in Surakarta City. This research is a descriptive qualitative type conducted in the Surakarta City area. The data used in this study are lingual units on coffee shop signboards in Surakarta City. Meanwhile, the data source in this research is the signboard of coffee shops in Surakarta City. The methods of data provision applied in this research are observation and interview methods. The techniques used in this research are systematically recording and documenting the symptoms that appear on the research object. The data that has been collected will be analyzed using the linguistic landscape analysis method by assessing the frequency of language use on coffee shop signboards. The presentation of data analysis results uses formal and informal descriptive methods. The results show that coffee shop names using multilingualism consist of Indonesian-English, Indonesian-Javanese, Indonesian-Japanese, Indonesian-Arabic, Indonesian-Dutch, Indonesian-German, Javanese-English, English-Sanskrit, English-French, English-Korean, English-Mandarin, English-Spanish, and English-Japanese.